2018
DOI: 10.1680/jmapl.18.00007
|View full text |Cite
|
Sign up to set email alerts
|

Briefing: Occupational safety and health regulations in Oman

Abstract: Poor occupational safety and health (OS&H) results in an economic burden of 4% of the total world gross domestic product (GDP). Effective OS&H regulations and their implementation are one of the main factors in achieving an improved safety performance. This article discusses the current OS&H regulations applicable in all industries including construction in Oman. Construction is one of the main industries in Oman, which contributes about 9% towards its GDP. This article attempts to offer some basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…Regarding health and safety in Oman, it"s imperative that we highlight that Health and Safety in Oman has been taken into consideration for quite a while now. Ministerial Decree 286/2008: Regulation of Occupational Safety and Health, was introduced to overlook the health and safety of industry operations (Umar et al, 2018). This regulation is the leading piece of legislation on Occupational Health and Safety in the Sultanate of Oman.…”
Section: Wwwijsseiin 344mentioning
confidence: 99%
“…Regarding health and safety in Oman, it"s imperative that we highlight that Health and Safety in Oman has been taken into consideration for quite a while now. Ministerial Decree 286/2008: Regulation of Occupational Safety and Health, was introduced to overlook the health and safety of industry operations (Umar et al, 2018). This regulation is the leading piece of legislation on Occupational Health and Safety in the Sultanate of Oman.…”
Section: Wwwijsseiin 344mentioning
confidence: 99%
“…This may significantly contribute towards the body pain in specific areas. While there have been several concepts and methods to improve safety performance and avoid accidents at construction site, safety culture and safety climate have attracted many researchers and practitioners worldwide due to its significant impact on the safety improvement (Kines et al, 2011, Umar and Egbu, 2018-c, Umar and Wamuziri, 2016. The safety culture represents the overall culture of an organization reflecting how safety is considered or treated.…”
Section: Improving Safety Performancementioning
confidence: 99%
“…Thus, it is important to know what is the cost of accidents and cost of prevention of accidents in construction. Similarly, the existence of the occupational health and safety regulations and its implementation in a country play a signification role in the reduction of occupational accidents(Umar et al 2018;Umar, 2018). For instance, in the United States, worker-deaths before the establishment of the…”
mentioning
confidence: 99%
“…The back, fingers, and hands were found to be the most commonly injured parts of the body among mechanical and electrical construction workers. Umar et al (2018) noted that the back of the body is among the top most frequently reported injury areas among general construction workers. The key areas of the body in which pain was reported in this study include the back (39.40%), knees (18.11%), shoulders (15.3%), legs (14.52%), and neck (12.37%).…”
Section: Introductionmentioning
confidence: 99%